The Current Portrayal of Non-Variceal Upper Gastrointestinal Bleeding in a Portuguese Tertiary Center - Falcão,Daniela (2021)
Abstract: Introduction: Non-variceal upper gastrointestinal bleeding (NVUGIB) is an important healthcare problem whose epidemiology and outcomes have been changing throughout the years. The main goal of this study was to characterize the current demographics, etiologies, and risk factors of NVUGIB. Methods: Analysis of clinical, endoscopic, and outcome data from patients who were admitted for NVUGIB between January 2016 and January 2019 in an emergency department of a tertiary hospital center. Results: A total of 522 patients were included, with a median age of 71 years, mainly men, with multiple comorbidities. Most patients were directly admitted, while the others were transferred from other hospitals. Peptic ulcer disease was the most common cause of NVUGIB and it was followed by tumor bleeding. Esophagogastroduodenoscopy was performed within <12 h after hospital admission in 51.9%. In-hospital rebleeding occurred in 6.9% and overall mortality was 4.2%. Transferred patients had superior Glasgow-Blatchford score (GBS), required more blood transfusion, endoscopic and surgical interventions, and presented higher rebleeding rate, with similar mortality. Complete Rockall score (CRS) and GBS were predictors of endoscopic therapy. Surgery need was only related to CRS. Patients who rebled had superior pre-endoscopic Rockall score (RS), CRS, and GBS. Mortality was increased in patients with higher RS and CRS. Discussion/Conclusion: Ageing and increasing comorbidities have not been related to worse outcomes in NVUGIB. These findings seem to be the consequence of the correct use of both diagnostic and therapeutic tools in an organized and widely accessible healthcare system.